Off-season physiological profiles of elite National Collegiate Athletic Association Division III male soccer players - Miller, D. K.; Kieffer, H. S.; Kemp, H. E.; Torres, S. E. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to develop a profile of soccer-related fitness parameters on elite National Collegiate Athletic Association (NCAA) Division III male soccer players during the off-season. Sixteen underclassmen from a recent NCAA Division III national championship soccer team completed a series of tests across 3 separate occasions over a 15-day period, with adequate recovery time between sessions to eliminate any carryover effect. Physiological parameters measured included aerobic endurance, anaerobic power and capacity, jumping power, agility, hamstring flexibility, and body composition. Descriptive statistics such as the mean (±SD) and range were calculated for each test. Two-tailed Pearson correlations were run to determine significant relationships that existed between variables. Test results were T-Tests (9.9 ± 0.4), Active Knee Extension degrees (-34.2 ± 11.9 right, -34.0 ± 13.9 left), vertical jump (61.8 ± 7.2 cm), percent fat (5.6 ± 1.6), Progressive Aerobic Cardiovascular Endurance Run (PACER) laps (113.2 ± 12.3), estimated Vo2max (53.6 ± 2.9 ml/kg/min), Wingate peak (802.7 ± 155.6 W), Wingate peak (10.9 ± 1.2 W/kg), Wingate mean (651.2 ± 101.6 W), Wingate mean (8.9 ± 0.6 W/kg), and Wingate fatigue rate (35.9 ± 8.4%). Strong correlations existed between PACER laps and percent fat, between peak W and peak W/kg, and between peak W and fatigue rate. These results suggest that elite Division III soccer players maintain relatively high fitness levels during the off-season. Additionally, they provide coaches with preliminary norms that can be used to determine off-season training expectations and adjust programs accordingly for their athletes.